Assessment of Microbial Contamination of Drinking Water in Kabul City - Ahmadi, Sayed arif (Journal of Natural Sciences – Kabul University, 2020)
The quality of drinking water plays a critical role in human health, as it can contribute to infections and diseases. Water is the most vital element for survival for many organisms, and contamination of drinking water with various pollutants and pathogenic microbes poses a major challenge. In this study, a total of 120 samples were collected from various sources of drinking water around Kabul City between 1/2/2016 and 2/3/2017. These samples were transferred aseptically to animal diagnostic research laboratories for analysis. The results showed that 75 of the 120 samples tested positive for different microorganisms, including 44 samples of Streptococcus, 9 samples of Pseudomonas aeruginosa, 10 samples of Hydrophilia, 3 samples of Citrobacter, and 1 infected sample.